Histopathologic evaluation of effects of systemic Strontium Ranelate of Pontastacus leptodactylusapplication on bone healing after grafting tibial defect - Karabulut, Burak; Tanrisever, Murat; Ozcan, Erhan Cahit; Koksaldi, Irem Semiha; Turgut, Burak; Istek, Ozmen; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2026)
Thisstudy evaluated the effectsofdifferent dosesof strontium useseriousproblemsinnatureDMTresiduesmixedwiththe quaticenvironmentadverselyaffectquaticganismsand ranelate combined with a bovine-derived deproteinized xenogeneic bone graft on bone healing in a rat defect model. s carreo umns roue oisffecti idth a th ghthfd cn s haiInthi Thirty-five female Sprague Dawley rats wererandomly assigned e to five groups (n = 7). A healthy control group received no udy, oxidative str s s re ponses induced by DMT pesticidein twere nvestigated.Forhispupose, treatment. In all other groups, a standardized 4 mm & times; 4 mm aixidative stress and nt ioxidant parameters Thiobarbitur c acid defect was created in the metaphyseal region of the rat tibia The idefect control group received no additional treatment. In act ve substances (TBARS), Glut ath one (GSH) Superoxide the defect-graft group, the defect was filled with a bovine lsm tase (SOD) cata ase (CAT) and glutathione p er xidase G derived deproteinizedxenogeneic bone graft. In the defect-PX)causedbydimethoate(DMT)pesticideingraft+ strontium groups,the defect was filled with the same-17.5,35,and70mgL-1concentratonsat24and96hours raftand strontium ranelate was administered by oral rere investigated. Results we e dete m ned us ing ELISA kits at doses of 450 mg/kg or 900 mg/kg, three times per week for ieight weeks. All rats were euthanized at the end of the eightiweek experimental period. Bone tissues were harvested and ere processed observed for between histological decreases analysis. in Data CAT and normality GPx was activities assessed and .creassinTBARSlevelsPSS240packageprogramone-way using the Shapiro-Wilk and Kolmogorov-Smirnov tests. As NOVA(Duncan005)wasusedintheevaluatonofbiochemical normality assumptions were not met, group comparisons were nalyzesAsaresult,itwasdeterminedthatDMTcausedoidative performed using the Kruskal-Wallis test followed by Mann-Whitney U post hoc tests. Mean horizontal defect sizes were 0 in the healthy control group, 716.86 in the defect group ress formation in ndcausedchanges in enzyme ctivities 658.57 in the defect-graftgroup, 604.57 in the defect-graft oeywordsDimethoate, , oxidative dose 1 group, and 598.86 in the dose 2 group. Mean vertical values were 0 in the healthy group, 575.14 in the defect group, 596.43 in the defect-graftgroup, 569 in the dose 1 group, and ssnoxetes,atiidant,biomakrs 503.29 in the dose 2 group. In conclusion, strontium ranelate had a positive effect on bone healing compared to the control group, particularly when combined with grafting. A significant difference was also observed between the defect group and the high-dose group, confirming its beneficial effect on bone . g-gavage ,
Keywords: Strontium ranelate; bone defect; bone grafting; guided bone regeneration; tibia bone; rat